Current Evidence on Dietary Factors and Kidney Allograft Function in Kidney Transplant Recipients: A Systematic Review - Nosrati-Oskouie, Mohammad; Salavatizadeh, Marieh; Ghorban Sabbagh, Mahin; Aghili-Moghaddam, Nazanin S.; Tarighat-Esfanjani, Ali; Sahebkar, Amirhossein (Current Medicinal Chemistry, 2024)
Background: Currently, there is no accounted-for consensus and practical standard when counseling diet modification for kidney transplant recipients (KTRs). There are many differences between transplant centers regarding what KTRs are needed to follow a diet, what dietary factors and supplements are allowed, and how long KTRs should follow a modified diet. Relatively few scatter data are available for dietary factors in KTRs. Thus, we aimed to systematically review the literature on the purported dietary factors for kidney function. Methods: A systematic literature search was performed between February and March 2022 and updated in February 2023 using PubMed, Scopus, Web of Science, and Google Scholar. We included human observational and interventional studies that evaluated a dietary factor on kidney function and graft survival in KTRs. Data were extracted, and the risk of bias was assessed using established tools relevant to the study design. Results: Of the 5341 citations retrieved, seven prospective cohorts, five cross-sectional, seventeen randomized, and ten non-randomized clinical trials were included that evaluated seven purported dietary factors. Almost half of the studies (n = 22; 56%) were classified as having a low degree of bias and sufficient support. Twenty-one studies (54%) reported a positive effect on KTRs. DASH and Mediterranean diets decreased graft failure, low-sodium diet reduced blood pressure, and antioxidants improved creatinine, GFR, and graft function. Of these, only twelve studies (31%) were at low risk of bias. Conclusion: Some dietary factors, including DASH, Mediterranean, moderate protein, and low– sodium diet, as well as antioxidants, may be associated with improved survival and kidney function in KTRs. However, more research is needed.
Keywords: vitamins